Case Report: Ultrasound-guided fine-needle aspiration for parathyroid cyst - Serblin, A.; Valcavi, R. (Frontiers in Radiology, 2025)
A 55-year-old man was referred to our Department with a cystic lesion in the lower right lobe of the thyroid, incidentally discovered on ultrasound. The mass measured 52.1 × 55.3 × 66.8 mm, with a volume of 93.2 mL, and caused significant tracheal indentation with contralateral deviation. The patient was asymptomatic and did not have dysphagia, hoarseness or dyspnoea. Ultrasound-guided fine-needle aspiration of the lesion yielded a clear, “rock-water” fluid. Biochemical analysis of the aspirate revealed elevated parathyroid hormone (PTH), leading to a diagnosis of a parathyroid cyst (PCs). This case highlights the importance of considering PCs in the differential diagnosis of large cystic neck masses, particularly when they mimic thyroid nodules. We report on this case and discuss the diagnostic challenges and management strategies for this rare condition. IntroductionParathyroid cysts (PCs) are uncommon benign neck masses, making up 1%–5% of all neck lumps and typically affecting women aged 40–60. While many cases are asymptomatic, they often present as a palpable mass in the neck, which can lead to misdiagnosis as a solitary thyroid nodule. Large cysts can cause compressive symptoms like difficulty swallowing, hoarseness, and tracheal deviation. Diagnosis involves imaging modalities like ultrasound, CT, and MRI to confirm the cystic nature of the mass. A key diagnostic step is fine-needle aspiration (FNA), where elevated parathyroid hormone (PTH) in the cyst fluid can confirm its parathyroid origin, even if blood PTH levels are normal. Treatment depends on whether the cyst is functional or causing symptoms. Options for non-functional cysts include aspiration or sclerotherapy, though recurrence is common. Surgical removal is the definitive treatment for functional cysts, symptomatic cysts, or when the diagnosis is uncertain. Minimally invasive techniques like radiofrequency ablation (RFA) and ethanol ablation (EA) are also effective, particularly for symptomatic non-functional cysts.MethodA 55-year-old male patient presented with an incidental finding of a right inferior thyroid cystic lesion measuring 52.1 mm (AP) × 55.3 mm (T) × 66.8 mm (Sag) with a volume of 93.2 mL on ultrasound examination. The patient underwent an ultrasound guided fine-needle aspiration (FNA) of the cystic formation. Approximately 90 mL of clear, “rock water”-colored fluid was extracted. To confirm the diagnosis of a parathyroid cyst, biochemical analysis of the aspirated fluid was performed. Parathyroid hormone (PTH) and thyroglobulin (Tg) levels were measured in the cyst fluid. The results showed a PTH concentration of 1,845.80 ng/L and a Tg level of 0.37 µg/L. Cytological analysis of the aspirated material revealed amorphous, acellular content. The combination of the high PTH concentration in the aspirate and the low Tg level confirmed the diagnosis of a non-functioning right inferior parathyroid cyst. A six-monthly follow-up ultrasound for 5 years was performed to assess for recurrence, which showed no evidence of fluid re-accumulation. Serum levels of calcium, PTH and vitamin D were measured, which were found to be normal both before and after the procedure.ResultsIn a 55-year-old male, an incidental ultrasound and fine-needle aspiration revealed a right inferior parathyroid cyst. Approximately 90 cc of clear, “rock water”-like fluid was drained, with fluid analysis confirming high parathyroid hormone (PTH) levels. Despite the cystic finding, both pre- and post-procedural plasma levels of PTH, calcium, and vitamin D remained within normal limits. This indicates a non-functioning cyst that did not disrupt systemic endocrine balance. A six-monthly follow-up ultrasound for 5 years showed no recurrence of the cystic lesion. These findings highlight that even large, PTH-rich parathyroid cysts can be non-functional and managed effectively with simple aspiration, often with no subsequent recurrence.DiscussionBased on the findings, we conclude that this case represents a non-functioning parathyroid cyst. The patient's normal plasma levels of PTH, calcium, and vitamin D both before and after the procedure confirm that the cystic lesion did not secrete hormones in a way that affected systemic metabolism. The successful management of the cyst with fine-needle aspiration and the subsequent absence of recurrence for 5 years with a six-monthly follow-up ultrasound demonstrate that this simple, minimally invasive approach can be an effective and definitive treatment for such lesions. This case report highlights that even large PCs can be non-functional and managed conservatively with excellent long-term results.